Mid-air hand interaction with optical tracking for 3D modelling - Cui, Jian (2019)
Compared to common 2D interaction done with mouse and other 2D-tracking devices, 3D hand tracking with low-cost optical cameras can provide more degrees of freedom, as well as natural gestures when shape modeling and assembling are done in virtual spaces. However, though quite precise, the optical tracking devices cannot avoid problems intrinsic to hand interaction, such as hand tremor and jump release, and they also introduce an additional problem of occlusion. This thesis investigates whether interaction during 3D modeling can be improved by using optical sensors so that 3D tasks can be performed in a way similar to interaction in real life and as efficient as when using common 2D-tracking based interaction while still minimizing the intrinsic problems of precise hand manipulations and optical problems.